1986
DOI: 10.1128/mcb.6.4.1117
|View full text |Cite
|
Sign up to set email alerts
|

Functional organization of the simian virus 40 origin of DNA replication.

Abstract: To define the sequence elements involved in initiation of DNA synthesis at the simian virus 40 origin of replication, we determined the relative replication efficiencies in vitro and in vivo of templates containing a variety of mutations within the origin region. Replication of the mutants in vitro was assayed by the cell-free DNA replication system that we recently described (J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
169
2

Year Published

1987
1987
1992
1992

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(186 citation statements)
references
References 74 publications
15
169
2
Order By: Relevance
“…1A). The ori core is the minimal SV40 sequence required for SV40 replication in vivo (12)(13)(14)(15)21) and in vitro (15,22) as well as ori-dependent DNA unwinding (22) and can be divided into three elements. These include a 15-bp imperfect inverted repeat (early palindrome), four contiguous GAGGC pentanucleotide sequences contained in a 27-bp perfect inverted repeat, and a 17-bp A/T-rich sequence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). The ori core is the minimal SV40 sequence required for SV40 replication in vivo (12)(13)(14)(15)21) and in vitro (15,22) as well as ori-dependent DNA unwinding (22) and can be divided into three elements. These include a 15-bp imperfect inverted repeat (early palindrome), four contiguous GAGGC pentanucleotide sequences contained in a 27-bp perfect inverted repeat, and a 17-bp A/T-rich sequence.…”
Section: Resultsmentioning
confidence: 99%
“…DNase I protection studies ("footprinting") have shown that T antigen bound to site I protects sequences from approximately nucleotide 5175 to 5215, while site II is protected from nucleotide 5215 to 35 (10,11). T antigen site II is essential for SV40 replication, since mutations in this region can completely inhibit replication in vivo and in vitro, whereas site I can be removed with less severe effects (12)(13)(14)(15). However, many studies examining T antigen interactions with the SV40 ori in vitro were performed under conditions that do not support replicatione.g., incubations were at low temperatures (usually 00C) and lacked ATP.…”
mentioning
confidence: 99%
“…The early domain is essential for both in vivo and in vitro replication. Its deletion reduces T-antigen-driven replication in COS-1 cell extracts 10-fold and SV40 replication in vivo 20-fold (24). Point mutants defective in replication also cannot bind the factor (41), suggesting a role for the early-domain-binding protein.…”
mentioning
confidence: 99%
“…Productive infection depends on prior synthesis of the viral T antigen (40). Replication starts at the viral origin (10,13,40), which spans a minimum of 64 base pairs (bp) (4,16,18,24,28,39) (Fig. 1).…”
mentioning
confidence: 99%
“…Because of the uncertainty concerning what constitutes a cellular origin of replication, information has come mostly from viral systems where the origins are defined genetically (6,10,21). Among the papova-and adenoviruses, the involvement of transcription regulatory elements in replication control is very well documented (12,25,31). Conversely, template replication is typically required for late gene transcription (9,19).…”
mentioning
confidence: 99%